Investigation of alkaloids of Anabasis aphylla (Chenopodiaceae) - HAMAD, M. N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The aerial part of Iraqi Anabasis aphylla (Chenopodiaceae) had been investigated for its alkaloidal contents.The alkaloid anabasine [2-(3-pyridyl)-piperidine] [1] & aphyllidine were isolated from an ethanolic extract of the plant. Isolation of the alkaloid was done by column chromatography followed by preperative thin layer chromatography. Identification of the isolated alkaloid was done by different spectroscopic methods (UV,IR), refractive index & TLC using authentic sample & preparation of a salt.